Genre Blending and Contract Design - Salmi-Tolonen Tarja (Edward Elgar Publishing, 2022)
Contracts are said to be the meeting of the minds. Thus far, there are few possibilities to share what is in the minds of the contracting parties to make such a meeting of minds tangible to the parties themselves and other audiences. This chapter is about the blending of conventional expressions of the minds – genres. I first explain how the concepts are used in this chapter and then discuss the present-day contractual genres in view of a model of five parameters and their dimensions. It is no news that the world and commerce are changing and, consequently, contracting and contracts are also changing. The realization of the changes becomes obvious slowly and incrementally because traditions and conventions represented by genres change slowly. Genres are not static or solid, but dynamic and continuously developed with every instance of contracting. The main concern here is in international commercial interfirm contracting, contract chains and their expression, although a large part of the discussion and suggestions are universally relevant.
Research Handbook on Contract Design